SIKAP BAHASA DAN MOTIVASI BELAJAR INDONESIA, BAHASA INGGRIS, DAN BAHASA ARAB SANTRI DI SEKOLAH PUTRI DARUL ISTIKAMAH KABUPATEN MAROS - Ginaya, Nurginaya (JURNAL ILMU BUDAYA, 2021)
This study aims to describe the language attitudes and motivation of students towards Indonesian, English and Arabic at the Darul Istikamah School for Girls (Spidi), Maros Regency. This research is descriptive qualitative quantitative. The population of this study were all students at SMA class XI and XII with a total of 65 students who had or temporarily participated in the total immersion program. The sampling technique is an entire sample. Collecting data through distributing questionnaires, observations, and interviews measured using a Likert scale. The results of the analysis show that the attitude of the students' language shows a positive attitude which is measured through three components of language attitudes, namely the cognitive component, the affective component, and the conative part of Indonesian, English and Arabic. The results showed that the instrumental motivation for learning the language of students towards Indonesian, English and Arabic was higher than the integrative motivation.